Pattern and Consequences of Examination Malpractice Among in School Adolescents in Kwara State : Study of teachers perception - Bolu-Steve, Foluke Nike; Uyanne, E O; Kayode, D (Buletin Konseling Inovatif, 2025)
This study examined the teachers’ perceptions on the pattern and consequences of examination malpractice among in-school adolescents in Kwara State. The descriptive survey design was adopted for this study. In each of the Senatorial districts in Kwara State, one hundred respondents took part in this study. Thus, a total of three hundred teachers participated in the study. Simple random technique was used in selecting the respondents. The researchers developed questionnaire titled Pattern and Consequences of Examination malpractice (PCEMQ) was administered to teachers. Six null hypotheses were tested using Analysis of Variance (ANOVA) and t-test statistical tool at 0.05 alpha level. The outcome of the study revealed that all the hypotheses were accepted. However, a significant difference was found in the pattern of examination malpractices based on gender. It is therefore recommended that school administrators should clearly spell out the rules and regulations guiding the conduct of examinations in schools. A constant reminder of these rules is expected to further strengthen compliance.